2022
DOI: 10.1177/20406207221112899
|View full text |Cite
|
Sign up to set email alerts
|

The development of pevonedistat in myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML): hope or hype?

Abstract: Myelodysplastic syndrome (MDS) is a clonal hematopoietic stem cell disorder clinically defined by cytopenias, bone marrow failure, and an increased risk of progressing to acute myeloid leukemia (AML). Traditionally, first-line treatment for patients with higher-risk MDS has been hypomethylating agents (HMAs). However, these agents have modest clinical activity as single agents. A one-size-fits-all treatment paradigm is insufficient for such a heterogeneous disease in the modern era of precision medicine. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Pevonedistat (TAK-924/MLN4924) is an inhibitor of the NEDD8 activating enzyme (NAE), which suppresses neddylation and induces cell cycle arrest and apoptosis [ 139 ]. Moreover, it increases the accumulation of the pro-apoptotic protein NOXA, as well as the upregulation of PUMA, BIK, and BIM [ 140 , 141 , 142 ]. However, the phase III PANTHER study (NCT03268954) of pevonedistat plus azacitidine ( n = 227) vs azacitidine ( n = 227) in patients with newly diagnosed higher-risk MDS, higher-risk chronic myelomonocytic leukemia, or AML with 20–30% blasts, failed to reach pre-defined statistical significance for the primary endpoint of event-free survival (EFS) [ 143 ].…”
Section: Targeting Neddylation In Amlmentioning
confidence: 99%
“…Pevonedistat (TAK-924/MLN4924) is an inhibitor of the NEDD8 activating enzyme (NAE), which suppresses neddylation and induces cell cycle arrest and apoptosis [ 139 ]. Moreover, it increases the accumulation of the pro-apoptotic protein NOXA, as well as the upregulation of PUMA, BIK, and BIM [ 140 , 141 , 142 ]. However, the phase III PANTHER study (NCT03268954) of pevonedistat plus azacitidine ( n = 227) vs azacitidine ( n = 227) in patients with newly diagnosed higher-risk MDS, higher-risk chronic myelomonocytic leukemia, or AML with 20–30% blasts, failed to reach pre-defined statistical significance for the primary endpoint of event-free survival (EFS) [ 143 ].…”
Section: Targeting Neddylation In Amlmentioning
confidence: 99%
“…MDS is generally recognized as a myeloid malignancy that usually occurs at an older age. 29 In a report by Candoni et al 30 , AML or MDS-contracted patients who were under treatment showed favorable seroconversion following the first 2 doses of the COVID-19 vaccine. More importantly, a large population of the selected patients experienced an alleviated seroconversion following the second dose of vaccination.…”
Section: Leukemia and Myelodysplastic Syndrome (Mds)mentioning
confidence: 98%